Early Diffusion of SARS-CoV-2 Infection in the Inner Area of the Italian Sardinia Island - Piras, Giovanna; Grandi, Nicole; Monne, Maria; Asproni, Rosanna; Fancello, Tatiana; Fiamma, Maura; Mameli, Giuseppe; Casu, Gavino; lo Maglio, Iana; Palmas, Angelo D.; Tramontano, Enzo (Frontiers in Microbiology, 2021)
Background: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has been responsible for coronavirus disease 2019 (COVID-19) pandemic, which started as a severe pneumonia outbreak in Wuhan, China, in December 2019. Italy has been the first European country affected by the pandemic, registering a total of 300363 cases and 35741 deaths until September 24, 2020. The geographical distribution of SARS-CoV-2 in Italy during early 2020 has not been homogeneous, including regions severely affected as well as administrative areas being only slightly interested by the infection. Among the latter, Sardinia represents one of the lowest incidence areas, likely due to its insular nature. Methods: Next generation sequencing of a small number of complete viral genomes from clinical samples and their virologic and phylogenetic characterization was performed. Results: We provide a first overview of the SARS-CoV-2 genomic diversity in Sardinia in the early phase of the March-May 2020 pandemic, based on viral isolated in the most inner regional hospital of the Island. Our analysis revealed a remarkable genetic diversity in local SARS-CoV-2 viral genomes, showing the presence of at least 4 different clusters that can be distinguished by specific amino acid substitutions. Based on epidemiological information, these sequences can be linked to at least 8 different clusters of infection, 4 of which likely originates from imported cases. In addition, the presence of amino acid substitutions which were not previously reported in Italian patients has been observed, asking for further investigations in a wider population to assess their prevalence and dynamics of emergence during the pandemic. Conclusions: The present study provides the first overview of SARS-CoV-2 epidemiology in inner area of the Sardinia island, suggesting a pivotal role of imported cases in its genomic diversity.